Unraveling the competitive transport of metformin and erythromycin in saturated sandy soil: Experimental investigation, modeling insights and implications on SDGs - Maliha Ashraf; Pankaj Kumar Gupta; Anushree Malik; Sumedha Chakma; Shaikh Ziauddin Ahammad (Journal of Hazardous Materials Letters)
The presence of metformin (MTN) and erythromycin (ETM) in groundwater is a growing global concern due to their persistence and toxicity. This study addresses a critical gap in understanding the fate and transport of these pharmaceutical and personal care products in saturated sandy soil columns at environmentally relevant concentrations, an underexplored area. The results show that MTN, due to its high mobility, appeared earlier in the soil column with a recovery rate exceeding 90 % and an adsorption coefficient (Kd) of 1.063 Lkg−1. In contrast, ETM, with a higher Kd value of 5.426 Lkg−1, exhibited delayed breakthrough and recovery of less than 15 %, indicating stronger adsorption potential. Desorption studies indicated a greater risk of MTN leaching into groundwater, while ETM remained strongly adsorbed to soil particles. Despite the limited organic matter content in sandy soil, a significant amount of ETM was adsorbed, suggesting sands' high adsorption capacity and potential for natural remediation. This research fills a knowledge gap regarding the adsorption capacity of sandy soils at environmentally relevant concentrations, providing essential insights for environmental risk assessments and groundwater contamination mitigation strategies, directly supporting Sustainable Development Goals 3 (Health and Well-being), 6 (Clean Water and Sanitation), and 14 (Life Below Water).